The White House Station of the Grand Paris Express Project. Issue 4 (1st October 2020) - Zhang, Yi; Commend, Stéphane; Martin-Lavigne, Quentin; Lacoste, Jérôme
Abstract: The White House Station of the Paris metro Line 14 is part of Grand Paris Express, the largest metro project underway in Europe. It includes an underground station, a tunnel built by conventional tunnelling methods and a connection to the existing Paris metro Line 7. This paper describes its structural design, risk and structural analyses, construction and monitoring. The project is located in a dense urban environment with high risks relating to geology (fractured limestone, swelling clay) and sensitive neighbouring structures (high-rise buildings and an existing metro line). Based on past experience and geotechnical analysis of the site investigations results, the design of the station included overcut diaphragm walls (1.5 m wide, 47 m deep), cross-walls (0.63 m wide, 6 m high) and slabs (20 m wide, 120 m long and 1.5 m thick). To understand the soil-structure interaction for the existing and new structures, a three-dimensional finite element model was developed and parametric studies were performed. Owing to planning restrictions, construction works were phased concurrently with a significant amount of demolition. To observe the real-time behaviour of soils and structures, a substantial monitoring system was utilised and continuous geotechnical observations were carried out.